2021
DOI: 10.3390/brainsci11030348
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to the Impact of the COVID-19 Pandemic on Working Memory, Empathy, and Perceived Stress: The Role of Cortisol and Resilience

Abstract: There are important individual differences in adaptation and reactivity to stressful challenges. Being subjected to strict social confinement is a distressful psychological experience leading to reduced emotional well-being, but it is not known how it can affect the cognitive and empathic tendencies of different individuals. Cortisol, a key glucocorticoid in humans, is a strong modulator of brain function, behavior, and cognition, and the diurnal cortisol rhythm has been postulated to interact with environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 115 publications
2
21
0
Order By: Relevance
“…Firstly, our research took place during the COVID-19 pandemic, with social distancing measures between and within military units being applied. This may have become an additional stressor which served to influence hair cortisol levels and perceived stress measurements, as has been shown in previous studies [56,57]. The results of the second phase (after four months of training) of our study and of Model 2 should be interpreted with caution, as the information contained there was collected during the national COVID-19 lockdown and it was not possible to have a control group to evaluate this effect.…”
Section: Discussionmentioning
confidence: 77%
“…Firstly, our research took place during the COVID-19 pandemic, with social distancing measures between and within military units being applied. This may have become an additional stressor which served to influence hair cortisol levels and perceived stress measurements, as has been shown in previous studies [56,57]. The results of the second phase (after four months of training) of our study and of Model 2 should be interpreted with caution, as the information contained there was collected during the national COVID-19 lockdown and it was not possible to have a control group to evaluate this effect.…”
Section: Discussionmentioning
confidence: 77%
“…In other words, the strength of the established associations was similar for all degrees of cortisol change among participants. By contrast, a study on 45 undergraduate psychology course students examined pre-pandemic salivary cortisol indices on the psychological impact of strict social confinement during the COVID-19 pandemic ( Baliyan et al, 2021 ). They showed that 41% of the variance in during-confinement perceived stress was predicted by total diurnal cortisol release, resilience score, and their interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings regarding depression and anxiety, 23 of the included publications (72%) indicated higher levels of stress or psychological stress among youth during the pandemic. Among the nine longitudinal studies on these problems, six indicated higher levels of (dis)stress (Baliyan et al, 2021;Breaux et al, 2021;Elmer et al, 2020;Gray et al, 2020;Magson et al, 2021;Savage et al, 2020), two indicated no significant changes (Copeland et al, 2021;Munasinghe et al, 2020), and one indicated a decrease in "acute stress" (but increases in depression and anxiety symptoms as reported above) (Y. .…”
Section: Youth Mental Health During Covid-19mentioning
confidence: 91%